Layu Sebelum Berkembang: Studi Kasus Kerjasama Sister City Malang dengan Fuqing dalam Komoditas Kedelai (Department of International Relations, Universitas Brawijaya, 2021)
The purpose of this paper is to determine the factors that have stopped the Sister City cooperation between Malang City and Fuqing City in the field of soybean commodity. Fulfilling the need for imported soybeans is important for Malang, because it is well-known for its many ‘Keripik Tempe’ producers or commonly called ‘IKM Tempe’, so that the potential for Fuqing imported soybean is important to be realized. The study used a qualitative descriptive method, and used the Paradiplomacy Concept and the Sister City Concept in explaining the cooperation between Malang City and Fuqing City. The results obtained were the cooperation between sister city Malang City and Fuqing City in the field of soybean commodity which ‘failed’ because soybeans from Fuqing were of lower quality than soybeans imported from United States and had large production losses, so that the IKM Tempe in Malang preferred to use imported United States soybeans and stopped the use of imported Fuqing soybeans. Until now, the two city governments have not been heard meeting to discuss this issue, which makes the city government as a sub-state actor not yet having a strong commitment to this cooperation.